Biofuels and economic development in Tanzania - Arndt, Channing; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2010)
Biofuels provide a new opportunity to enhance economic development in Tanzania. Drawing on detailed cost estimates, we develop a dynamic computable general equilibrium model to estimate the impact of different biofuel production scenarios on growth and poverty. Our results indicate that maximizing the poverty-reducing effects of a biofuels industry in Tanzania requires engaging and improving the productivity of smallholder farmers. Evidence shows that cassava-based ethanol production is more profitable than other feedstock options. Our findings also indicate that cassava generates higher levels of pro-poor growth than do sugarcane-based systems. However, if smallholder yields can be improved rather than expanding cultivated land, then sugarcane and cassava outgrower schemes can produce similar pro-poor outcomes. We conclude that in so far as the public investments needed to establish a biofuels industry in Tanzania are in accordance with national development plans, producing biofuels will contribute to achieving the country's overall development objectives.